Semantics of Lexicology in the Study of Arabic Phonemes and Lexemes - Nailul Izzah; M Agus Mushodiq; Muhammad Syaifullah (Mantiqu Tayr: Journal of Arabic Language, 2021)
Linguistics is the name of the field of science, and the adjective is linguistic. Meanwhile in Arabic, the linguistic equivalent is known as Ilmu lughah or al-lisaaniyyat. The study of language is generally directed at four discussions. First, regarding the sounds of language. If the research of language sounds is carried out without looking at the sound function it is known as phonetic, whereas if the study of language sounds by looking at the sound function in language it is known as phonology. Second, the study of the form of the word (sharf). In the sharf, it is studied about changing the words of a language, where this science is known as morphology. Third, discussion of sentence structure (nahwu). The scope of study in Nahwu is the wording of a sentence in a language, this knowledge is known as syntax or grammar. Fourth, discussion about the good meaning of a word, sentence, or the meaning of an expression. This science is called semantics. Linguistics can be divided into two major branches, namely micro linguistics and macro linguistics. The object of micro linguistic study is the internal structure of the language itself, including the structure of phonology, morphology, syntax, and lexicon. While the object of factors outside of language is such as sociological, psychological, anthropological, and ethnolinguistic factors. The author will only discuss phonology (phoneme) and lexicology (lexeme) in an Arabic linguistic study using library research methods.